2016
DOI: 10.1038/npp.2016.21
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Social Isolation Stress Increases Kappa Opioid Receptor Responsiveness and Downregulates the Dopamine System

Abstract: Chronic early-life stress increases vulnerability to alcoholism and anxiety disorders during adulthood. Similarly, rats reared in social isolation (SI) during adolescence exhibit augmented ethanol intake and anxiety-like behaviors compared with group housed (GH) rats. Prior studies suggest that disruption of dopamine (DA) signaling contributes to SI-associated behaviors, although the mechanisms underlying these alterations are not fully understood. Kappa opioid receptors (KORs) have an important role in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 60 publications
7
107
0
Order By: Relevance
“…Activation of KORs reduces dopamine release in the NAc (Ebner et al, 2010; Werling et al, 1988). In another recent study, we showed that KOR-mediated inhibition of dopamine release was enhanced in aSI compared to aGH rats (Karkhanis et al, 2016). These data suggest that aSI results in increased functional responsiveness of KORs in the NAc which may contribute to the observed increase in EtOH intake.…”
Section: Nucleus Accumbensmentioning
confidence: 86%
See 2 more Smart Citations
“…Activation of KORs reduces dopamine release in the NAc (Ebner et al, 2010; Werling et al, 1988). In another recent study, we showed that KOR-mediated inhibition of dopamine release was enhanced in aSI compared to aGH rats (Karkhanis et al, 2016). These data suggest that aSI results in increased functional responsiveness of KORs in the NAc which may contribute to the observed increase in EtOH intake.…”
Section: Nucleus Accumbensmentioning
confidence: 86%
“…Importantly, aSI also leads to robust, long-lasting increases in multiple measures of voluntary EtOH drinking (Chappell et al, 2013; McCool and Chappell, 2009; Skelly et al, 2015) and enhances EtOH CPP (Whitaker et al, 2013). In addition, 2 studies have examined the pharmacology of EtOH drinking in aSI rats and reported that anxiolytic medications targeting the noradrenergic system and KORs significantly attenuated binge-like EtOH drinking in aSI rats at doses that had no significant effect in aGH subjects (Karkhanis et al, 2016; Skelly et al, 2015). Collectively, these findings provide promising initial evidence that this model has both face and predictive validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been postulated that a shift in hedonic set point is driven, in part, by hyperactivity of the dynorphin/KOR system in dependent animals (Bruchas et al, 2010). Thus it is possible that KOR blockade, which decreases ethanol intake selectively in dependent animals (Walker and Koob, 2008; Walker et al, 2011; Rose et al, 2015) and in animals exposed to chronic early-life stress (Karkhanis et al, 2016), relieves the negative affective state that the animals is in, potentially by normalizing dopamine system function.…”
Section: Discussionmentioning
confidence: 99%
“…Although some incongruous studies have revealed that repeated exposure to opioids and stressors reduces dopamine release in the NAc and inhibits sensitization (Karkhanis et al, 2016;Kaufling and Aston-Jones, 2015). This raises the question: which paradigms lead to sensitization?…”
Section: Introductionmentioning
confidence: 99%